Investigation on the Sources and Impact of Trace Elements in the Annual Snowpack and the Firn in the Hansbreen (Southwest Spitsbergen) - Spolaor, Andrea; Moroni, Beatrice; Luks, Bartłomiej; Nawrot, Adam; Roman, Marco; Larose, Catherine; Stachnik, Łukasz; Bruschi, Federica; Kozioł, Krystyna; Pawlak, Filip; Turetta, Clara; Barbaro, Elena; et al. (Frontiers in Earth Science, 2021)
We present a thorough evaluation of the trace element composition (Ca, Sr, Mg, Na, K, Li, B, Rb, U, Ni, Co, As, Cs, Cd, Mo, Se, Eu, Ba, V, Ge, Ga, Cr, Cr, P, Ti, Mn, Zr, Ce, Zn, Fe, Gd, Y, Pb, Bi, Yb, Al, Nb, Er, Nd, Dy, Sm, Ho, Th, La, Lu, Tm, Pr, Tb, Fe, In, Tl) and fluxes in the annual snowpack and the firn ice of the Hansbreen glacier (a tidewater glacier terminating in the Hornsund fjord, southwest Spitsbergen). The trace element samples were obtained from a 3 m deep snow pit dug at the plateau of the glacier (450 m a.s.l.), and from a 2 m deep firn core collected from the bottom of the snow pit. Based on the results of the flux calculations, dust deposition was shown to be a significant source of impurities to the annual snow and firn, in addition to maritime sources, which are predominant. Trace metals were mostly related to the dust cycle and therefore they could be used to differentiate and qualitatively resolve the contribution of local and long-range transport sources of impurities to the annual snowpack. The comparison of elemental fluxes and enrichment factors allowed us to constrain specific summer and wintertime deposition patterns of trace elements in the southern part of the Svalbard archipelago.